DEVELOPMENT OF INTRA-GOVERNMENTAL NETWORKS ACEH JAYA DISTRICT BASED ON CLOUD COMPUTING - Pania, Sadri; Wibawa, M. Bayu; Yusian TB, Desita Ria (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2025)
The development of an intra-government network in Aceh Jaya Regency based on cloud computing aims to increase efficiency and flexibility in managing government internet network services. This study develops and implements an intra-government network system that uses cloud computing technology to improve service quality and network management efficiency. The results of the study indicate that the development of an intra-government network based on cloud computing can increase efficiency and flexibility in managing government network systems, as well as improve the quality of service to regional devices in Aceh Jaya Regency.